Innovations in Soil Fertilization and the Role of Remineralizers - Santos, Luiz Fernando dos; Abrantes, Ewerton Gonçalves de; Marchi, Giuliano; Martins, Éder de Souza (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – To review the role of soil remineralizers (REM) in tropical soil fertility, focusing on CEC, organic carbon, and environmental mitigation potential.Methodology – Literature review using scientific databases (Web of Science and Google Scholar), selecting studies on REM, CEC, and carbon dynamics.Originality/relevance – The study addresses gaps in understanding charge generation and carbon stability in tropical soils amended with REM, highlighting its relevance for sustainable agriculture.Results – REM increase CEC, improve nutrient availability, and contribute to carbon stabilization in soils.Theoretical/methodological contributions – Advances in the understanding of bioweathering and mineral–organic matter interactions in soils.Social and environmental contributions – Reduction in dependence on chemical inputs, promotion of rock-based agriculture, and mitigation of environmental impacts.
Keywords: Agricultural sustainability; Soil management; Rock powder